Information and communication technologies and the production, distribution and use of knowledge. (1st January 2000) - Antonelli, Cristiano; Geuna, Aldo; Steinmueller, W. Edward
The interaction between the development of information and communication technologies and the evolution of the organisation of the generation of new knowledge is twofold. Information and communication technologies change the process and the organisation of the accumulation of new knowledge. The new conditions for the accumulation of technological knowledge and the elaboration of an appropriate institutional and organisational set-up in turn do affect the pace and direction of the technological convergence upon which the evolution of information and communication technologies rests.